Lipid metabolism and cancer - Bian, Xueli; Liu, Rui; Meng, Ying; Xing, Dongming; Xu, Daqian; Lu, Zhimin (The Journal of experimental medicine, 2021)
Dysregulation in lipid metabolism is among the most prominent metabolic alterations in cancer. Cancer cells harness lipid metabolism to obtain energy, components for biological membranes, and signaling molecules needed for proliferation, survival, invasion, metastasis, and response to the tumor microenvironment impact and cancer therapy. Here, we summarize and discuss current knowledge about the advances made in understanding the regulation of lipid metabolism in cancer cells and introduce different approaches that have been clinically used to disrupt lipid metabolism in cancer therapy.